2013
DOI: 10.1124/mol.113.090365
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase–Activated Protein Kinase 2 in Neuroinflammation, Heat Shock Protein 27 Phosphorylation, and Cell Cycle: Role and Targeting

Abstract: Mitogen-activated protein kinase (MAPK)-activated protein kinase 2 (MAPKAPK-2 or MK2) is a downstream substrate of the p38 MAPK responsible for the signaling events influencing inflammation, cell division and differentiation, apoptosis, and cell motility in response to a wide range of extracellular stimuli. After the failure of p38 MAPK inhibitors in clinical trials, MK2 was unveiled as a potential target to regulate inflammatory cytokines' mRNA stability and translation. Recent work suggests that this mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 143 publications
(159 reference statements)
2
60
0
Order By: Relevance
“…In addition, based on our finding of upregulated MAPK1, which we validated, we also quantified its related kinases pMAPK1 and pMAPKAPK2 [52] by Western blotting. We found these proteins to be upregulated following prenatal inflammation, in agreement with the current literature [68][69][70] , and decreased following preventative treatment. The MAPK pathway is known to be highly implicated in the cellular response to inflammation [71] , and it has been linked to myelin formation where gain of MAPK1 function promotes central nervous system developmental myelination [40] .…”
Section: Discussionsupporting
confidence: 80%
“…In addition, based on our finding of upregulated MAPK1, which we validated, we also quantified its related kinases pMAPK1 and pMAPKAPK2 [52] by Western blotting. We found these proteins to be upregulated following prenatal inflammation, in agreement with the current literature [68][69][70] , and decreased following preventative treatment. The MAPK pathway is known to be highly implicated in the cellular response to inflammation [71] , and it has been linked to myelin formation where gain of MAPK1 function promotes central nervous system developmental myelination [40] .…”
Section: Discussionsupporting
confidence: 80%
“…MAPKs include extracellular signal-regulated kinases (ERK-1 and -2), JNKs and p38 (Gurgis, Ziaziaris, & Munoz, 2014). Previous studies have recognized that JNK and p38 MAPK are primarily involved in LPS-induced expression of iNOS and COX-2 in macrophages (Kwon, Ju, Youn, Choi, & Park, 2013;Kyriakis & Avruch, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, excellent surveys of the studies on the biology of p38/MK2 pathway have been reported, 2-5 also describing the efforts made to find new and effective MK2 inhibitors. 2,4,23 In this review, the most important classes of small molecules able to inhibit MK2 by an ATP-competitive and a non-ATP-competitive mechanism are reviewed.…”
Section: Introductionmentioning
confidence: 99%